(untitled) (Trinity Journal of Management, IT & Media (TJMITM), 2022)
The impact of the COVID-19 pandemic on education is vast, ranging from the adoption of online classes to better understanding the nature of the rapid institutional transition during the pandemic situation.The pandemic has resulted in reduced academic attainment and unfinished learning, which had a profound effect on the future economic prospects of millennials. In fact, the pandemic had shown the potential to thwart the plans of many millennials to go to college and find a rewarding career to support themselves and their families. While the effects were diverse, the cumulative cost of unfinished learning and achievement gaps were greater than the current investments made. But, the sudden shift in institutional teaching methodologies and conditions created around the education industry created the dilemmas about the results that will be demonstrated by the two groups of university faculty, separately identified as novice online teachers and expert online teachers. This case study aims to provide useful accounts of the changes that occurred in interconnected teaching activity systems at the university while adopting online teaching, highlighting the complex factors underpinning individual academics’ experiences. The case study focuses on a ‘deep dive’ into the challenges faced by teachers in conducting distance-learning activities while schools were closed.Finally, the case study presents lessons learned and recommendations on how to strengthen systems to provide a stronger education sector to bridge the gap between the reality and ambitions of India’s education policy.